Enhancing GridFTP performance using intelligent gateways. (21st October 2008) - Demir, Onur; Head, Michael R.; Ghose, Kanad; Govindaraju, Madhusudhan
To improve throughput of grid data servers under heavy loads or under denial of service attacks, it is important to service requests differentially, giving preference to ongoing or imminent client requests. We show how such features can be efficiently implemented on a gateway that controls access to a pool of servers. We present performance results for a prototype system based on a dual-ported active NIC, and demonstrate that an efficient differentiated service policy can be implemented on such a gateway to minimise the grid service response time and to improve server throughputs under heavy loads and denial of service attacks.